2014
DOI: 10.1002/dys.1476
|View full text |Cite
|
Sign up to set email alerts
|

Are Dyslexic Children Sensitive to the Morphological Structure of Words When They Read? The Case of Dyslexic Readers of French

Abstract: Typically, research has cited a deficient use of word recognition procedures mainly caused by a phonological deficit as the source of dyslexic students' reading difficulties. However, recent studies have shown that morphological processing also plays an important part in reading. In the present study, sensitivity to the morphological structure of words was assessed with a plausibility judgment task, where participants determined which of two pseudo-words most resembled a real word in French, and with a decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
0
13
0
2
Order By: Relevance
“…This is in sharp contrast to Quémart and Casalis (2015) results that showed that dyslexic French children have developed representations for written morphology and that these representations are activated rapidly and automatically during visual recognition of morphologically complex words. Berthiaume and Daigle (2014) did note some morphological sensitivity among their French dyslexic children aged 9–12 years but also that they were outperformed by both reading-level and same-age peers. The lack of consistency in the results described may be due to methodological differences, such as selected tasks and age or control groups.…”
Section: Morphological Complexitymentioning
confidence: 86%
See 2 more Smart Citations
“…This is in sharp contrast to Quémart and Casalis (2015) results that showed that dyslexic French children have developed representations for written morphology and that these representations are activated rapidly and automatically during visual recognition of morphologically complex words. Berthiaume and Daigle (2014) did note some morphological sensitivity among their French dyslexic children aged 9–12 years but also that they were outperformed by both reading-level and same-age peers. The lack of consistency in the results described may be due to methodological differences, such as selected tasks and age or control groups.…”
Section: Morphological Complexitymentioning
confidence: 86%
“…Reading is a complex activity requiring the processing of graphic information in order to achieve optimal text comprehension (Berthiaume and Daigle, 2014). The simple view of reading, a model suggested by Gough and Tunmer (1986) and Hoover and Gough (1990), in short holds that reading comprehension skills can be predicted from two components: decoding abilities, defined as efficient visual word recognition, and linguistic comprehension, which is the ability to use information at the lexical or word level to achieve sentence and discourse interpretations (Hoover and Gough, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le phonème à l'oral, le graphème à l'écrit, la syllabe orale ou écrite et le morphème oral ou écrit constituent des unités sublexicales qui permettent de former des mots (Ziegler & Goswami, 2005). La sensibilité du lecteur/scripteur à ces types d'unités sublexicales orales et écrites est essentielle au développement de la lecture et de l'écriture, comme l'ont montré de nombreuses recherches (voir, par exemple, Berninger, Abbott, Nagy & Carlisle, 2010 ;Berthiaume & Daigle, 2014 ;Caravolas & Landerl, 2010). La connaissance du sens d'un mot renvoie aux concepts et aux référents qui y sont associés.…”
unclassified
“…Children with dyslexia have been shown to perform below chronological-age-(CA-) matched peers on morphological awareness measures in many languages (Berthiaume & Daigle, 2014;Carlisle, 1987;Casalis et al, 2004;Duranovic, Tinjak, & Turbic-Hadzagic, 2014;Egan & Pring, 2004;Egan & Tainturier, 2011;Joanisse, Manis, Keating, & Seidenberg, 2000;Leong, 1999;McBride-Chang et al, 2008;McBride-Chang, Liu, Wong, Wong, & Shu, 2012;Shu, McBride-Chang, Wu, & Liu, 2006;Siegel, 2008;Tsesmeli & Seymour, 2006;Vogel, 1977). They have also been shown to use morphological processes (in reading and spelling) less than age-matched peers Carlisle, Stone, & Katz, 2001;Fisher, Shankweiler, & Liberman, 1985;Hauerwas & Walker, 2003;Leong, 1989).…”
mentioning
confidence: 99%